2012
DOI: 10.2478/v10213-012-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determinaton of Fluoroquinolones in Feed by Liquid Chromatography with Fluorescence Detection

Abstract: An HPLC method with fluorescence detection (HPLC-FLD) was developed for the simultaneous quantitative determination of enrofloxacin, ciprofloksacin, sarafloxacin, and difloxacin in feed. The samples were extracted with 0.25% formic acid in ultrasonic bath and purified by solid phase extraction (SPE) on Strata-X cartridges. The samples were analysed on Luna C8 liquid chromatography column with gradient programme by acetonitrile and 0.025 M phosphoric acid with 0.0025 M sodium 1- heptanesulfonate monohydrate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, data from the literature and Rapid Alert System for Food and Feed (RASFF) indicated that there were incidents of ENR illegal use in laying hens' therapy (15). Many analytical methods for determination of ENR in animal tissues, feed, milk, and egg have been described (6,10,13,14). Nevertheless, none of the developed methods concerns analysis of these compounds in albumin and freeze-dried-eggs.…”
Section: Introductionmentioning
confidence: 99%
“…However, data from the literature and Rapid Alert System for Food and Feed (RASFF) indicated that there were incidents of ENR illegal use in laying hens' therapy (15). Many analytical methods for determination of ENR in animal tissues, feed, milk, and egg have been described (6,10,13,14). Nevertheless, none of the developed methods concerns analysis of these compounds in albumin and freeze-dried-eggs.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our experiments showed that 0.1% formic acid was the best additive for increasing peak resolution and sensitivity. Most published methods used acetonitrile as an organic solvent mobile phase for the analysis of an antibacterial compound (Gbylik et al, 2012). In this study, the best results were obtained utilizing a gradient elution and a chromatographic column with acetonitrile and 0.1% formic acid in Milli-Q water.…”
Section: Optimization Of Uhplc-ms/ms Conditionsmentioning
confidence: 95%
“…In previously reported methods, the excitation/emission wavelengths for most FQs were generally set to 278/445 nm or 280/465 nm [5,32]; in addition, a few methods have used excitation/emission wavelengths of 293/500 nm for LEV and MOX [37]. A single set of excitation and emission wavelengths does not allow optimized detection of all FQs.…”
Section: Optimizing the Fluorescence Response Of Fluoroquinolonesmentioning
confidence: 99%
“…Mobile phases containing nonvolatile acids or salts have been shown to suppress FQ ionization [7,17,27,28]. As many chromatography methods [5,7,15,[29][30][31][32][33][34] have employed phosphate buffers to reduce FQ peak asymmetry, this eluent limitation can negatively affect FQ peak shape during LC-MS/MS analysis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation